(untitled) (Our Nature, 2021)
The present research was conducted for quantitative study and diversity analyses of aquatic macrophytes dwelling littoral zone of Jagadishpur reservoir, Kapilvastu district in three seasons, as winter (December), summer (April), and rainy (August). Altogether 58 species of macrophytes were recorded in study site, of which highest number of species (54) was occupied by angiosperms followed by three species of pteridophytes and one species of alga. These macrophytes varied in different morphological groups, viz., emergent, submerged, and rooted-floating leaf type. Maximum number of species were represented by emergents (39) followed by rooted-floating leaf type (12) and submerged (7) macrophytes. There was distinct seasonal variation in the distribution of macrophytes: based on importance value index, Nelumbo nucifera (IVI = 22.87), Scripus sp. (IVI = 28.01), Ipomoea carnea (IVI = 24.67) and Typha angustifolia (IVI = 29.01) were dominant in the winter; Nelumbo nucifera (IVI = 20.05), Cynodon dactylon (IVI = 20.07) and Ipomoea carnea (IVI = 21.17) were dominant in the summer and Nelumbo nucifera (IVI = 23.8) and Scripus sp. (IVI =25.56) were dominant in the rainy season. The highest species diversity (H’) of macrophytes was observed during summer (3.451), followed by rainy season (3.135) and winter (3.008). The luxuriant growth of aquatic macrophytes evidenced the highly productive nature of the lake, while the dominance of emergents among the growth forms indicates the encroachment of littoral vegetation, indicating a successional trend toward marsh meadow.